The growing complexity of content delivery networks: Challenges and implications for the Internet ecosystem. Issue 10 (November 2017) - Stocker, Volker; Smaragdakis, Georgios; Lehr, William; Bauer, Steven
Abstract: Since the commercialization of the Internet, content and related applications, including video streaming, news, advertisements, and social interaction have moved online. It is broadly recognized that the rise of all of these different types of content (static and dynamic, and increasingly multimedia) has been one of the main forces behind the phenomenal growth of the Internet, and its emergence as essential infrastructure for how individuals across the globe gain access to the content sources they want. To accelerate the delivery of diverse content in the Internet and to provide commercial-grade performance for video delivery and the Web, Content Delivery Networks (CDNs) were introduced. This paper describes the current CDN ecosystem and the forces that have driven its evolution. We outline the different CDN architectures and consider their relative strengths and weaknesses. Our analysis highlights the role of location, the growing complexity of the CDN ecosystem, and their relationship to and implications for interconnection markets. Highlights: We describe the current CDN ecosystem and the forces that have driven its evolution. We describe different CDN architectures and their relative strengths and weaknesses. The growing complexity of the CDN ecosystem is illustrated. Implications for interconnection markets are discussed.